Voltammetric behavior of a chemically modified carbon paste electrode with cadmium nitroprusside prepared in different water to formamide ratios - Souza, Tamires Rocha [UNESP]; de Sá, Acelino Cardoso; dos Santos Franco, Fernanda [UNESP]; Barbosa, Priscila Fernanda Pereira [UNESP]; Andrade, Rômulo Davi Albuquerque; da Costa, Fabíola Medeiros [UNESP]; Carvalho, Kamilla Alves [UNESP]; de Oliveira, Denys Ribeiro [UNESP]; Cumba, Loanda Raquel; Paim, Leonardo Lataro [UNESP]; Vieira, Eduardo Guimarães; do Carmo, Devaney Ribeiro [UNESP] (Elsevier, 2020)
This paper describes a voltammetric study of cadmium nitroprusside synthesized from different compositions of water/formamide in your reaction of Cd2+ with [FeIII(CN)5NO]2- (CdNP). After infrared and transmission electron microscopy characterization, the CdNP was incorporated into a carbon paste electrode and a systematic voltammetric study was performed for four systems (CdNP-1, CdNP-2, CdNP-3 and CdNP-4). The spectroscopic studies reveals that all preparations was conducted with success. The cyclic voltammogram of all CdNP particles obtained from a carbon paste electrode modified (10% m/m) exhibited a redox couple with formal potential (Eθ') = 0.63 ± 0.02 V (10 % (m/m); v=20 mV s-1; KNO3 1.0 M) attributed to the redox process [FeII(CN)5NO]/[FeIII(CN)5NO] in the presence of Cd2+.
Keywords: Cadmium nitroprusside; Eletro-oxidation; Formamide; Isoniazid; Voltammetry